Overview of lenvatinib as a targeted therapy for advanced hepatocellular carcinoma - Rehman, Obaid; Jaferi, Urooj; Padda, Inderbir; Khehra, Nimrat; Atwal, Harshan; Mossabeh, Dina; Bhangu, Ranvir (Clinical and Experimental Hepatology, 2021)
Hepatocellular carcinoma (HCC) is the fifth most common malignancy worldwide. Patients commonly present with advanced/unresectable HCC where several treatment options are not effective. In this review, the authors discuss the indications and usage of lenvatinib, a multikinase inhibitor, as first-line therapy for advanced/unresectable HCC, its mode of action, efficacy, drug reactions, response to treatment and adverse effects. Since its approval in 2007, sorafenib has been used as first-line therapy for unresectable HCC. In 2018, a phase III multinational REFLECT trial on subjects with unresectable HCC (Child-Pugh class A) demonstrated that lenvatinib was non-inferior compared to sorafenib for overall survival, with a controllable toxicity profile, leading to its approval. In addition, our review discusses studies that compare the safety and efficacy profile of lenvatinib especially in patients who have a decline in their liver function to Child-Pugh class B. A current real world analysis of lenvatinib approval for unresectable HCC worldwide is reported.